Peningkatan Pengetahuan tentang Bahaya HIV/AIDS dengan Permainan Kartu di Pondok Pesantren - Firmansyah; Riska Ayu Nur Azizah; Ade Kustika; Ernawati; Sahrul Reza Husaeni; Siti Latifah; Adi Nurapandi (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: HIV is a virus that attacks the immune system, the cause of the emergence of AIDS which will make it difficult for the human body to fight disease due to a weakened immune system. Every year new cases continue to be found and West Java occupies the fourth position with the most cases in Indonesia during 2020. Objective: to increase the knowledge of students about the dangers of HIV/AIDS and invite them to jointly prevent it Method: The activities carried out were pretest, educational card game, quiz discussion, and posttest. This game uses card media consisting of 36 cards for two groups, each group gets 18 cards. The cards consist of 6 quiz cards, 6 correct answer cards, and 6 wrong answer cards. The quiz on the card is a quiz about HIV/AIDS. Then all participants are invited one by one to come forward to take a quiz card and look for the right answer card within 10 seconds. Result: The knowledge of the students of the Al-Hasan Islamic Boarding School has increased with the implementation of community service programs through the media of this card game. Where almost all correspondents can answer the quiz correctly after playing the game. They can find out more about what HIV/AIDS is, so that they can prevent the occurrence of HIV/AIDS in their surrounding environment. Conclusion:  This educational card game can increase the knowledge of students who are still lacking about HIV/AIDS. With a fun method they can better understand and know how to respond to HIV/AIDS.